Mental fatigue and impaired response processes: Event-related brain potentials in a Go/NoGo task - Kato, Yuichiro; Endo, Hiroshi; Kizuka, Tomohiro (International journal of psychophysiology, 2009)
The effects of mental fatigue on the availability of cognitive resources and associated response-related processes were examined using event-related brain potentials. Subjects performed a Go/NoGo task for 60 min. Reaction time, number of errors, and mental fatigue scores all significantly increased with time spent on the task. The NoGo-P3 amplitude significantly decreased with time on task, but the Go-P3 amplitude was not modulated. The amplitude of error-related negativity (Ne/ERN) also decreased with time on task. These results indicate that mental fatigue attenuates resource allocation and error monitoring for NoGo stimuli. The Go- and NoGo-P3 latencies both increased with time on task, indicative of a delay in stimulus evaluation time due to mental fatigue. NoGo-N2 latency increased with time on task, but NoGo-N2 amplitude was not modulated. The amplitude of response-locked lateralized readiness potential (LRP) significantly decreased with time on task. Mental fatigue appears to slows down the time course of response inhibition, and impairs the intensity of response execution.